Abordaje odontológico de la coinfección por sarcoma de kaposi y candidiasis oral en pacientes con vih: consideraciones clínicas para el cuidado dental. revisión sistemática - Oñate Silva, Ana Paulina (2025)
Oral diseases, such as Kaposi's Sarcoma and Oral Candidiasis, are common manifestations in people with HIV/AIDS and reflect immunological deterioration. Their presence indicates progression of the infection and efficacy of antiretroviral treatment, highlighting the importance of a comprehensive dental approach to improve the patient's oral and general health. Objective: The purpose of this article was to analyze the most effective approaches for the dental approach to the coexistence of Kaposi's Sarcoma and Oral Candidiasis in patients with HIV, with the purpose of providing evidence-based recommendations to improve the quality of dental care. Methodology: A systematic review of different databases such as PubMed, Google Scholar, Scielo, Sciencedirect was used, which helped to collect the relevant information for the development of the topic. Keywords were used to help identify articles that meet the inclusion and exclusion criteria. Results: The bibliographic review reveals studies that analyze the clinical approach to Kaposi's sarcoma and Oral Candidiasis in patients with HIV. Both present distinctive manifestations, specific treatments and comprehensive dental requirements. Conclusion: Kaposi's sarcoma and oral candidiasis co-infection in patients with HIV requires multidisciplinary management, with emphasis on prevention, early diagnosis and collaborative treatment to improve their quality of life.